Thermal safety model of HMX-based explosives in diamond turning. (July 2021) - Cao, Z.M.; Zong, W.J.; He, C.L.; Huang, J.H.; Liu, W.; Wei, Z.Y.
Graphical abstract: Highlights: Diamond turning of explosives has a new scientific safety control strategy. Frictional heat generation of cutting interface determines safety process criterion. A model predicts the safe cutting zone of explosives by thermal decomposition. Limit turning experiment for explosives confirms validity of theoretical model. Abstract: In this work, a comprehensive model was established to predict the thermal safety of polymer-bonded explosives (PBXs) in diamond turning. The thermal safety model not only considers the geometrical parameters of diamond tool and process parameters, but also integrates the kinetic law of friction-induced chemical reaction of PBXs chips. Moreover, the Arrhenius thermal decomposition of PBXs chips and its turning Logistic retardation growth model were also unified successfully, and the temperature measurement tool, thermal analysis tests and surrogate face cutting experiments were implemented separately. According to the controllable self-acceleration safe cutting criterion, this novel model reliably predicts the safe cutting zone of HMX-based PBXs. Finally, the turning experiments of PBXs validated that: (1) The combination of high cutting velocity and cutting temperature can induce a sufficient amount of PBXs chips to release uncontrollable chemical energy; (2) The frictional heating interface between the HMX crystal and the diamond tool tip is the most hazardous zone; (3) A reliable evaluation for the turning safety of PBXs requires detailed analyses on the cutting energy, friction time and hot spot distribution, which can be characterized by the theoretical model and cutting curve of T-v .